Method for evaluating the snagging propensity of roofing membranes in buildings by roosting bats. Issue 8 (16th November 2020) - Essah, E. A.; Russell, S. J.; Waring, S. D.; Ferguson, J.; Williams, C.; Walsh, K.; Dyer, S.; Raynor, R.
ABSTRACT: Many buildings suitable as bat roosts contain synthetic roofing materials, hereafter referred to as Non-Bitumen Coated Roofing Membranes (NBCRMs) – this includes Breathable Roofing Membranes (BRMs) and non-Permeable Roofing Membranes (nPRMs), rather than 1F felts. Building regulations require all construction materials to be fit for purpose, but some BRMs (although appropriate for their intended purpose) can potentially threaten the viability of existing, legally protected roosts because of the way bats physically interact with their surface. With the assistance of the Isle of Wight Bat Hospital and real-world observations of how bats physically interact with NBCRMs within a roof void, we present a new laboratory test method capable of reproducing the progressive disintegration of NBCRM surfaces due to the plucking effect of bat claws. The resistance to NBCRM disintegration was characterized using a modified laboratory fabric pilling box test method. The method reproduced the 'fluffing' effects and projections of loops of filaments on the surface of BRMs that have been observed within bat roosts. It was established that spunbond nonwoven BRMs, can be highly susceptible to surface disintegration. The newly developed method is intended to aid selection of NBCRMs that reduce the risk to bats in their roosts, promoting bat conservation.